Edukasi Pemeliharaan Dokumen Rekam Medis di Ruang Filing - Pomarida Simbolon; Angela Br Surbakti; Angeli Br Surbakti; Eva Vanya Theresia Br Tarigan; Lusiana Simanjorang; Teofilus Rivaldo Zagoto (Vitamin : Jurnal ilmu Kesehatan Umum, 2024)
Medical record documents become a source of information for health workers in carrying out data analysis, planning, making decisions to provide services and become accountability files for proof of services that need to be maintained until the time limit according to agreed and established rules. The stages of activities carried out consist of the preparation and implementation stages. , and evaluation. The preparation stage includes a pre-test questionnaire, preparation of material by the facilitator, preparation of educational media in the form of banners and leaflets as well as a post-test questionnaire which is carried out the day before the counseling is carried out. The implementation stages include the delivery of educational material regarding maintaining medical record documents in the archive room. From the results of the percentage analysis, there was an increase in the percentage of students' overall knowledge of all aspects of medical record maintenance education in the application room delivered by the facilitator. Educational activities regarding how to maintain medical record documents in the submission room for Health Information Management study program students increased knowledge. knowledge increased by 18.61 points after health education was implemented. This increase in the average knowledge value occurred because health education used methods and medians, namely lectures and discussions.